Achieving Multidimensional Educational Goals Through Standard-Oriented Teaching. An Application to STEM Education - Schiepe-Tiska, Anja; Heinle, Anna; Dümig, Paula; Reinhold, Frank; Reiss, Kristina (Frontiers in Education, 2021)
Socially and in relation to the individual, schools’ mission for STEM education is not limited to the teaching of knowledge and cognitive skills. Although they form an important basis for dealing with today’s challenges in a self-confident and responsible manner, they alone are not enough. Positive attitudes towards learning are additional important prerequisites for lifelong learning and participation in society. However, national educational standards still focus mainly on developing cognitive competencies. They hardly take into account multidimensional educational goals that combine both cognitive and non-cognitive outcomes. At the classroom level, in everyday school life, addressing both is one of the greatest challenges. Introducing standard-oriented curricula may have the potential to shift teachers’ professional perception also to non-cognitive educational goals. We argue that, in order to foster multidimensional educational goals, they need to be more clearly addressed at the policy, teacher training, and teaching level. One important research agenda within STEM education for the next years will be to examine and discuss the connection between the implementation of standard-oriented teaching, the achievement of multiple educational goals, and teachers’ professional competence.